Genotyping of clinically relevant human adenoviruses by array‐in‐well hybridization assay. (19th June 2012) - Ylihärsilä, M.; Harju, E.; Arppe, R.; Hattara, L.; Hölsä, J.; Saviranta, P.; Soukka, T.; Waris, M.
<x xml:space="preserve">Abstract</x> Clin Microbiol Infect Abstract A robust oligonucleotide array‐in‐well hybridization assay using novel up‐converting phosphor reporter technology was applied for genotyping clinically relevant human adenovirus types. A total of 231 adenovirus‐positive respiratory, ocular swab, stool and other specimens from 219 patients collected between April 2010 and April 2011 were included in the study. After a real‐time PCR amplification targeting the adenovirus hexon gene, the array‐in‐well assay identified the presence of B03 (n = 122; 57.5% of patients), E04 (29; 13.7%), C02 (21; 9.9%), D37 (14; 6.6%), C01 (12; 5.7%), C05 (5; 2.4%), D19 (4; 1.9%), C06 (2; 0.9%), D08 (1; 0.5%), A31 (1; 0.5%) and F41 (1; 0.5%) genotypes among the clinical sample panel. The typing result was obtained for all specimens that could be amplified (n = 223; 97%), and specificity of the typing was confirmed by sequencing specimens representing each of the different genotypes. No hybridization signal was obtained in adenovirus‐negative specimens or specimens with other viruses (n = 30). The array‐in‐well hybridization assay has great potential as a rapid and multiplex platform for the typing of clinically relevant human adenovirus genotypes in different specimen types.